The use of resuscitative endovascular balloon occlusion of the aorta to control hemorrhagic shock during video-assisted retroperitoneal debridement or infected necrotizing pancreatitis. - Weltz, Adam S. (Int J Surg Case Rep, 2015)
INTRODUCTION: Resuscitative endovascular balloon occlusion of the aorta (REBOA) is a technique that has been shown to provide central vascular control to support proximal aortic pressure and minimize hemorrhage in a wide variety of clinic settings, however the role of REBOA for emergency general surgery is less defined. CASE DESCRIPTION: This is a report of a 44 year old man who experienced hemorrhagic shock during video-assisted retroperitoneal debridement (VARD) for necrotizing pancreatitis where REBOA was used to prevent ongoing hemorrhage and death. DISCUSSION: This is the first documented report REBOA being used during pancreatic debridement in the literature and one of the first times it has been used in emergency general surgery. The use of REBOA is an option for those in hemorrhagic shock whom conventional aortic cross-clamping or supra-celiac aortic exposure is either not possible or exceedingly dangerous. CONCLUSION: REBOA allows for adequate resuscitation and can be used as a bridge to definitive therapy in a range of surgical subspecialties with minimal morbidity and complications. The risks associated with insertion of wires, sheaths, and catheters into the arterial system, as well as the risk of visceral and spinal cord ischemia due to aortic occlusion mandate that the use of this technique be utilized in only appropriate clinical scenarios.